2007
DOI: 10.1080/16506070701223289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Experimentally Induced Positive and Anxious Mood on Alcohol Expectancy Strength in Internally Motivated Drinkers

Abstract: The effects of musically-induced positive and anxious mood on explicit alcohol-related cognitions (alcohol expectancy strength) in 47 undergraduate students who consume alcohol either to enhance positive mood states (for enhancement motives) or to cope with anxiety (for anxiety-related coping motives) were investigated. Pre- and post-mood induction, participants completed the emotional reward and emotional relief subscales of the Alcohol Craving Questionnaire - Now. The hypothesis that anxiety-related coping m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“… We acknowledge that some studies have reported mood influences on explicitly measured PAEs (e.g., Birch et al., 2004; Grant and Stewart, 2007). However, these studies tend to measure explicit PAEs with instruments keyed to be more sensitive to dynamic changes in PAEs (e.g., “right now, alcohol would…”).…”
mentioning
confidence: 99%
“… We acknowledge that some studies have reported mood influences on explicitly measured PAEs (e.g., Birch et al., 2004; Grant and Stewart, 2007). However, these studies tend to measure explicit PAEs with instruments keyed to be more sensitive to dynamic changes in PAEs (e.g., “right now, alcohol would…”).…”
mentioning
confidence: 99%
“…One large study of 85,301 schoolchildren (Meier, Slutske, Arndt, and Cadoret, 2007) found that positive alcohol expectancies mediated 45% of the association between delinquency and the initiation of drinking, and to a lesser degree binge drinking. Expectancy per se is not all explanatory, as recent work has demonstrated an interaction between expectancy, individual traits (Borders, Barnwell, and Earleywine, 2007), dispositional aggressivity (Giancola, 2006), mood (Grant and Stewart, 2007), context (Read and Curtin, 2007), and gender (Fossos, Neighbors, Kaysen, and Hove, 2007).…”
Section: Expectanciesmentioning
confidence: 95%
“…Craving and depressed mood interact to predict relapse (Cooney et al., ; Miller et al., ). While common maladaptive cognitive processes underlie both stress and depression, including increased attention to threat and punishment cues, their role in relapse is hypothesized to be distinct (Cassin and Rector, ; Fergusson et al., ; Grant and Stewart, ; Gullo and Stieger, ). Animal and human studies demonstrate stress can acutely trigger craving directly through sensitization of reward pathways (Koob and Le Moal, ).…”
mentioning
confidence: 99%